Glutamatergic regulation of brain histamine neurons: In vivo microdialysis and electrophysiology studies in the rat - Fell, Matthew J.; Flik, Gunnar; Dijkman, Ulrike; Folgering, Joost H.A.; Perry, Kenneth W.; Johnson, Bryan J.; Westerink, Ben H.C.; Svensson, Kjell A. (Neuropharmacology, 2015)
The interactions between the glutamatergic and the histaminergic systems in the brain are not fully understood. Here we studied histamine release in the medial prefrontal cortex and the posterior hypothalamus-tuberomamillary nucleus (PH-TMN) using in vivo microdialysis and electrophysiological recordings of histaminergc neurons in the PH-TMN in vivo to further address the mechanistic details of these interactions. We demonstrated that histaminergic activity was regulated by group II metabotropic glutamate receptors (mGluR 2 and 3) using systemic dosing with mGluR 2/3 agonist and antagonists and an mGluR 2 positive allosteric modulator. These interactions likely occur via direct modulation of glutamate release in the PH-TMN. The importance of circadian rhythm for histamine release was also shown using microdialysis studies with mGluR 2/3 compounds under light and dark conditions. Based on histamine release studies with NMDA and ketamine, we propose the existence of two sub-populations of NMDA receptors where one subtype is located on histaminergic cell bodies in the PH-TMN and the second on GABA-ergic neurons projecting to the PH-TMN. These subpopulations could be distinguished based on function, notably opposing actions were seen on histamine release in the medial prefrontal cortex of the rat. In summary, this paper provides evidence that the histaminergic system is closely regulated by glutamate neurons in multiple ways. In addition, this interaction depends to a great extent on the activity state of the subject.